Motor City Movie Culture, 1916-1925 - Abel, Richard (Book collections on Project MUSE., 2020)
"Motor City Movies, 1916-1925 is a broad textured look at Hollywood coming of age in a city with a burgeoning population and complex demographics. Richard Abel investigates the role of local Detroit organizations in producing, distributing, exhibiting, and publicizing films in an effort to make moviegoing part of everyday life. Tapping a wealth of primary source material-from newspapers, spatiotemporal maps, and city directories to rare trade journals, theater programs, and local newsreels-Abel shows how entrepreneurs worked to lure moviegoers from Detroit's diverse ethnic neighborhoods into the theaters. Covering topics such as distribution, programming practices, nonfiction film, and movie coverage in local newspapers, with entr'actes that dive deeper into the roles of key individuals and organizations, this book examines how efforts in regional metropolitan cities like Detroit worked alongside California studios and New York head offices to bolster a mass culture of moviegoing in the United States"--